A. (x+3)(4x+5)
(multiply x with 4x+5 then multiply 3 with 4x+5)
=4x^2+5x+12x+15
=4x^2+17x+15
b,c, and d are similar
Answer: 30 kilograms
explanation: Each 1000 grams converts to 1 kilogram
Answer:
60km
Step-by-step explanation:
They travel 30km in the first hour, then turn back and travel the same 30km backwards.
Answer: 24:34
Step-by-step explanation:
If you multiply the ratio by 2, for example, it will still be equal.
Answer:
f(g(x)) = 3(2x^3 -2)^2 - 4x + 2, and f(g(3)) = 3[2(3)^3 -2]^2 -4*3 -2 = 8102
Step-by-step explanation:
because for f(g(x)), the g(x) is the input of f(x), so put 2x^3 -2 into 3x^2 -4x +2, and you will get f(g(x)). because g(3) is the input of f(x), so find g(3) first, the answer is 52, and then put it back into f(x) which will be f(52) =[3(52)^2 - 4(3) +2], then the answer should be 8102.